Activity of Antioxidant Enzymes in Euphorbia heterophylla Biotypes and their Relation to Cross Resistance to ALS and Protox Inhibitors - XAVIER,E. (2018)
ABSTRACT: The characteristics of multiple resistance in Euphorbia heterophylla biotypes to herbicides that are inhibitors of ALS (Acetolactate synthase) and PPO (Protoporphyrinogen oxidase) and their responsible mechanisms are still not completely elucidated. The objectives of this study were to identify cross-resistance to herbicides from different chemical groups of ALS inhibitors (imidazolinones, sulfonylureas, pyrimidyl benzoates and sulfonanilides) and also PPO inhibitors (diphenylethers, phthalamides, oxadiazoles, triazolinones and pyrimidinediones) in E. heterophylla biotypes with multiple resistance to these herbicides; to analyze whether the antioxidant enzymes superoxide dismutase (SOD) and peroxidase (POD) constitute mechanisms that are responsible for the resistance to PPO inhibitors. Initially, the response to doses of herbicides from these different chemical groups was determined, using doses below and above the one recommended for the species. The control of E. heterophylla was determined, estimating the required doses for a 50 and 80% control reduction and calculating the resistance factors. The constitutive and induced activities of the SOD and POD enzymes were also determined. The results confirmed cross-resistance for all chemical groups of ALS and PPO inhibitors in the Bom Sucesso do Sul and Vitorino biotypes. The constitutive and induced activities of the SOD and POD enzymes were superior in plants from the E. heterophylla biotypes Vitorino and Bom Sucesso do Sul, contributing to their resistance to PPO inhibiting herbicides.